Nilai-nilai Tradisi Ratik Tolak Bala di Tandikek - Nurfitria Dewi; Yulius Yulius; Ahmad Nisam (Jurnal Budi Pekerti Agama Islam, 2023)
Tandikek is a hilly area in Padang Pariaman district. Tradition cannot be separated from the traces of human travel, as a characteristic form found in a social group and formed naturally which continuously reproduces practices in the process of interaction. With a disaster or disaster occurring in the midst of the Tandikek Community, the Community will carry out the Ratik tradition of rejecting evil. Tandikek people believe in this tradition, because of the existence of supernatural powers. This is what makes them always carry out the tradition of 'resist evil'. The first problem in this article is the role of the Ratik tradition in repelling reinforcements for the Tandikek Community. The theory used in this problem is the Redcliffe-Brown functional structural theory, which states that aspects of social behavior do not develop for individual needs, but to maintain the social structure of society. The tradition of ratik rejecting reinforcements at tandikek is one of the local wisdoms. The ratik tradition of rejecting reinforcements has maintained and fostered social ties among the Tandikek community. Society realizes that there must be harmony between humans and supernatural beings.